The World Enigma - Moody, Cary C. (Harvard theological review, 1924)
The enigma of the world is the existence of evil or imperfection. Though a deeper insight discloses relative perfection, yet the relative perfection of finite things discloses imperfection. If good of the kind, yet the kind is bad. There is no compliment more distasteful than to be told that one is good of his kind, for it implies that the kind may be bad.While it is obvious that the world, as a whole, is under the sway of one principle, yet the problem is how can a perfect being originate and sustain a world of imperfect beings, endowed with the capacity to develop towards perfection, and likewise with the capacity to resist such development?